Bridges over troubled waters: Climate clubs, alliances, and partnerships as safeguards for effective international cooperation? - Heiner von Luepke; Karsten Neuhoff; Catherine Marchewitz (International Environmental Agreements: Politics, Law and Economics, 2024)
AbstractDriven by the motivation to raise the ambition level of climate action and to foster the transformation of economies, current climate policy discourse revolves around ways to improve cooperation between industrialized countries and emerging economies. We identify three broad types of initiatives—multilateral-cross sectoral, multilateral, sector specific, and climate and development partnerships—and assess them for potentials to deliver on such objectives with a specific focus on industry transformation. This paper provides new reflections on the institutionalization of international climate cooperation. Specifically, we demonstrate the urgent need to understand what values, norms, and underlying principles drive a cooperation in order to draw conclusions on how to best institutionalize climate cooperation rules.in-use. We conclude that an overemphasis on a CO2 price and on carbon border adjustment mechanisms, such as in the context of the initial proposals for a cross-sectoral climate club envisaged by G7 countries, would have contributed to a further polarization of the international landscape. We find, however, that multilateral, sectoral alliances play an important role for international goal setting and the convergence on standards, metrics, and benchmarks. Based on our analysis, we recommend strengthening multilateral, sector-specific partnerships. These can be focused on sectoral topics as a connector between countries, allowing for a strategically-aligned, increasingly deep collaboration. However, for any initiative to succeed, processes of international institutionalization will be needed in order to agree on rules for implementation based on aligned interests and equity. Building such institutions may well serve as a steppingstone toward more durable cooperation structures between developed economies and emerging economies. In sum, no existing cooperation approach is perfect, but three actions may be taken to move the agenda forward: First, reform of the carbon border adjustment mechanism and removing it from the center of climate club discussions, second, coupling sectoral alliances with climate and development partnerships, and three, designing them in a way to address fears of political influence seeking and superimposition of global north agendas on the global south.
Keywords: 330; Global climate cooperation; Climate alliances; Climate partnerships; Carbon leakage; Industry decarbonization